-8+6(3g+6)=

Simple and best practice solution for -8+6(3g+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8+6(3g+6)= equation:


Simplifying
-8 + 6(3g + 6) = 0

Reorder the terms:
-8 + 6(6 + 3g) = 0
-8 + (6 * 6 + 3g * 6) = 0
-8 + (36 + 18g) = 0

Combine like terms: -8 + 36 = 28
28 + 18g = 0

Solving
28 + 18g = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + 18g = 0 + -28

Combine like terms: 28 + -28 = 0
0 + 18g = 0 + -28
18g = 0 + -28

Combine like terms: 0 + -28 = -28
18g = -28

Divide each side by '18'.
g = -1.555555556

Simplifying
g = -1.555555556

See similar equations:

| 180=y-4 | | -3x-8y+20y=5x+19 | | 4x^2-2x-120=0 | | 11x-4=11+2 | | 4(-5x-6)=-4 | | x/5+17=20 | | 2(7-4x)=-74 | | 9y^2+27y+14= | | 7(-7x+8)=-483 | | 12x+23=71 | | x^3=167 | | 17.00+5.50h=11.00+6.75h | | 98=7x-7 | | 4y-5y=81 | | 10+4c=5(c-6)+33 | | 5+(-24)= | | 2.5d+7.75=4+3.25d | | 6(x+3)-4(x-3)= | | 3w^2(w^2+3)=8+7w^2 | | 13x+2=54 | | 835=5x^3 | | 360=106+84+y+38+3y+12 | | 5+7*5+5= | | 4x-8=4x+-36 | | 4d=9-d-8 | | 5+2*5+5= | | -2(-4+x)=20 | | 2x+2=6x-10 | | 6log(x)=9 | | m=15C+10 | | 29=8x-11 | | 166=4n |

Equations solver categories